Relationships between cognitive appraisals of adolescents with OCD and their mothers - Kadak, Muhamrned Tayyib; Balsak, Fuat; Besiroglu, Lutfullah; Celik, Cihat (W B Saunders Co-Elsevier Inc, 2014)
Objective: Our aim was to investigate cognitive models of OCD via the influence of mothers' cognitive appraisals on children's cognitions and OCD symptoms. Method: Our sample consisted of 21 adolescents with OCD, their mothers and 27 parent child dyads for control group without OCD. Subjects with OCD and their mothers were administered The Beck Depression Inventory (BDI), The Thought Action Fusion Scale (TAFS), The White Bear Suppression Inventory (WBSI), The Padua Inventory-Revised (PI-R) and The Penn Inventory of Scrupulosity (PIS). Results: While the BDI (t = 2.18, p < 0.05) and TAF Morality (t = 2.18, p < 0.05) scores of the mothers of OCD subjects were significantly higher than the mothers of control subjects, the comparisons for the PI, TAF likelihood and PIOS scores of groups were not significant. Intradyadic correlation revealed significant relationships for PI-Rumination, PI-Checking and WBSI scales between the scores of parent and child in OCD dyads, (respectively, r = 0.49, P = 0.11; r = 0.37, P = 0.045; and r = 0.47, P = 0.014). There was no significant relationship in the control group. Conclusion: Our results partially supported that mothers' cognitive appraisals are associated with the cognitive appraisal of adolescents. A cognitive intradyadic interaction between mother and child might be more likely in the presence of OCD in adolescents. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Obsessive-Compulsive Disorder; Thought-Action Fusion; Psychometric Properties; Symptoms; Family; Onset; Inventory; Beliefs; Turkish; Responsibility